Defect passivation perovskite solar cell and preparation method thereof
The defect problem in perovskite solar cells was solved by the SnO2 method doped with organic hydrochloride and the perovskite absorption layer preparation method that spin-coated lead iodide and then spin-coated organic salt, and the photoelectric conversion efficiency was significantly improved.
Patent Information
- Application Number
- CN202411752744.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-18
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
Planar positive perovskite solar cells are prone to defects such as vacancy, gap and inverse position, resulting in shallow energy level defects, hindering the extraction and transmission of charges, and there is a problem of lattice mismatch and energy level mismatch between SnO2 and perovskites.
By doping organic hydrochloride with SnO2, high-quality SnO2 and perovskite films were prepared, and the precursor solution containing lead iodide was first spin-coated and then spin-coated the organic salt solution to react to form a perovskite absorbing layer, effectively achieving passivation of defects.
The photoelectric conversion efficiency of perovskite solar cells was improved, the open circuit voltage increased from 1.09V to 1.13V, the filling factor increased from 76.06% to 79.14%, and the photoelectric conversion efficiency increased from 19.45% to 21.72%, a relatively increase of 11.7%.
Smart Images

Figure CN119604170A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cell preparation, and in particular to a defect-passivated perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have a series of advantages such as simple preparation process, low cost, abundant raw materials, direct band gap and high photoelectric conversion efficiency, and have gradually become the most promising representative of solar cells. Perovskite materials are usually ABX 3 Structure, the A-site ion is usually formamidine ion (Formamidine, FA + ), methylamine ion (Methylamine, MA + ) or cesium ion (Cs + ) etc.; B-site ions are usually divalent metal ions such as lead ions and tin ions; X is usually halogen ions such as iodine ions, bromide ions, or chloride ions. Perovskite materials are a kind of direct bandgap semiconductor materials with adjustable composition. Compared with crystalline silicon (indirect bandgap), they have less phonon absorption and high light absorption coefficient (10 5 cm -1 ), large carrier diffusion distance (>1μm), small exciton binding energy (~50meV), high carrier mobility (100cm 2 V -1 s -1 ) and high defect tolerance, the photoelectric conversion efficiency of perovskite solar cells has rapidly increased from 3.8% in 2009 to 26.7% today. At present, the device structure of perovskite solar cells is divided into a formal structure (nip) and a transverse structure (pin). Among them, the commonly used formal structure is mainly a planar positive structure, which usually has a conductive glass substrate (ITO, FTO, etc.), an electron transport layer (SnO 2 、TiO 2 It consists of five parts: perovskite layer, hole transport layer (Spiro-OMeTAD, PTAA, P3HT, etc.), and electrode (Ag, Au).
[0003] Planar positive perovskite solar cells still have some shortcomings: (1) SnO 2 During the annealing process, vacancies (V O 、V Sn ), gap (O i , Sn i ), anti-site (SnO, OSn) and other defects. (2) Perovskite materials are organic-inorganic hybrid materials, which are very easy to form shallow energy level defects during spin coating and annealing, such as uncoordinated Pb 2+ , Pb-I antisite, metallic lead clusters, I- Defects such as vacancies. These defects will form charge recombination centers, hindering the extraction and transfer of charges. (3) SnO 2 There are problems such as lattice mismatch and energy level mismatch between perovskite and SnO, which affect the further improvement of efficiency. Therefore, in order to obtain perovskite solar cells with excellent photoelectric conversion efficiency, it is necessary to prepare high-quality SnO 2 Together with perovskite thin films, the performance and stability of perovskite solar cells can be synergistically improved. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a defect-passivated perovskite solar cell and a preparation method thereof, so as to solve the problems that the existing planar positive perovskite solar cells are prone to form defects such as vacancies, gaps and anti-sites, and are prone to produce shallow energy level defects, which hinder the extraction and transmission of charges. 2 There are problems of lattice mismatch and energy level mismatch with perovskite.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A method for preparing a defect-passivated perovskite solar cell comprises the following steps:
[0007] (1) SnO 2 The aqueous solution and the organic hydrochloride solution were mixed and ultrasonicated to obtain organic hydrochloride-doped SnO 2 Precursor solution;
[0008] (2) preparing a halogen compound solution and an organic salt solution as a perovskite precursor solution;
[0009] (3) Fk209, tributyl phosphate, lithium salt, Spiro-OMeTAD and chlorobenzene or tributyl phosphate, lithium salt, P3HT and chlorobenzene are uniformly mixed to obtain a hole transport layer precursor solution;
[0010] (4) On the substrate material, the organic hydrochloride-doped SnO 2 The precursor solution, the perovskite precursor solution obtained in step (2) and the hole transport layer precursor solution obtained in step (3) are used as raw materials for spin coating to prepare SnO 2 An electron transport layer, a perovskite absorption layer and a hole transport layer are prepared, and finally a molybdenum oxide layer and a silver electrode are prepared on the hole transport layer.
[0011] Furthermore, in step (1), SnO 2 The mass concentration of the aqueous solution is 1-5%; the organic hydrochloride includes any one of pentamidine hydrochloride, chloromethylamine, methoxyamine hydrochloride, propylamine hydrochloride and 3-chloropropylamine hydrochloride; the solvent of the organic hydrochloride solution is isopropanol or water; SnO2 The volume ratio of the aqueous solution to the organic hydrochloride solution is 1-2:1-50.
[0012] Further, the concentration of the pentamidine hydrochloride solution is 3-7 mg / mL, and the solvent is isopropanol; the concentration of any one of the solutions of chloromethylamine, methoxyamine hydrochloride, propylamine hydrochloride and 3-chloropropylamine hydrochloride is 15-25 mg / mL, and the solvent is water.
[0013] Preferably, the concentration of the pentamidine hydrochloride solution is 5 mg / mL, and the solvent is isopropanol; the concentration of any one of the solutions of chloromethylamine, methoxyamine hydrochloride, propylamine hydrochloride and 3-chloropropylamine hydrochloride is 20 mg / mL, and the solvent is water.
[0014] The beneficial effect of adopting the above further technical solution is: the present invention dopes SnO with organic hydrochloride 2 Method to prepare high-quality SnO 2 The perovskite film has effectively improved the efficiency of perovskite solar cells. The electron transport capacity of the electron transport layer has been improved by doping with organic hydrochloride, thereby effectively improving the carrier extraction capacity and further improving the photoelectric conversion efficiency of the device. 2 After that, the open circuit voltage of the perovskite solar cell increased from the original 1.09V to 1.13V; the fill factor increased from 76.06% to 79.14%, and the photoelectric conversion efficiency increased from the initial 19.45% to 21.72%, a relative increase of 11.7%.
[0015] Furthermore, in step (2), the halogen-containing compound is lead iodide or a mixture of lead iodide and cesium iodide, and the organic salt is iodomethylformamidine, chloromethylamine, or a mixture of iodomethylformamidine, chloromethylamine, and iodomethylamine; the solvent of the halogen-containing compound solution is a mixed solvent of DMF and DMSO or isopropanol, the concentration of lead iodide is 600-700 mg / mL, and the concentration of cesium iodide is 0-25 mg / mL; the solvent of the organic salt solution is isopropanol, and the mass ratio of the organic salt iodomethylformamidine to chloromethylamine is 70-100:6-20, or the mass ratio of iodomethylformamidine, chloromethylamine, and iodomethylamine is 50-100:8-12:6-12.
[0016] Preferably, the halogen compound solution is a lead iodide solution with a concentration of 692 mg / mL or a mixed solution of lead iodide with a concentration of 742.2 mg / mL and cesium iodide with a concentration of 19.8 mg / mL, and the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 9:1;
[0017] The organic salt solution is a mixed solution of 90 mg / mL iodomethylformamidine, 9 mg / mL chloromethylamine and 6.39 mg / mL iodomethylamine, and the solvent is isopropanol; or a mixed solution of 90 mg / mL iodomethylformamidine and 18 mg / mL chloromethylamine, and the solvent is isopropanol.
[0018] Furthermore, in step (3), the mass volume ratio of Spiro-OMeTAD, Fk209, tributyl phosphate, lithium salt solution and chlorobenzene is 65-80 mg: 5-15 mg: 20-40 μL: 25-45 μL: 0.5-2 mL; the mass volume ratio of P3HT, tributyl phosphate, lithium salt solution and chlorobenzene is 10-20 mg: 20-40 μL: 25-45 μL: 0.5-2 mL.
[0019] Preferably, in step (3), the mass volume ratio of Spiro-OMeTAD, Fk209, tributyl phosphate, lithium salt solution and chlorobenzene is 72.3 mg: 9 mg: 30 μL: 35 μL: 1 mL; the mass volume ratio of P3HT, tributyl phosphate, lithium salt solution and chlorobenzene is 15 mg: 30 μL: 35 μL: 1 mL.
[0020] Furthermore, the lithium salt solution is an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide with a concentration of 200-300 mg / mL.
[0021] Preferably, the lithium salt solution is an acetonitrile solution of lithium bistrifluoromethanesulfonyl imide with a concentration of 260 mg / mL.
[0022] Furthermore, in step (4), the substrate material is ITO transparent conductive glass, which is subjected to ozone treatment before spin coating, and the treatment time is 10-40 minutes.
[0023] Preferably, in step (4), the substrate material is ITO transparent conductive glass, which is subjected to ozone treatment before spin coating for 20 minutes.
[0024] Furthermore, in step (4), SnO 2 The spin coating speed of the electron transport layer is 3000-6000 rpm, the spin coating time is 10-60s, and the coating is annealed at 90-170°C for 15-45min; in the perovskite absorption layer, the spin coating speed of the halogen compound solution is 1000-2000 rpm, the spin coating time is 10-60s, and the coating is annealed at 50-90°C for 0.5-5min; the spin coating speed of the organic salt is 1500-3000 rpm, the spin coating time is 10-60s, and the coating is annealed at 100-150°C for 10-30min; the spin coating speed of the hole transport layer is 1500-5000 rpm, the spin coating time is 10-60s, and the oxidation time is 1-15 hours.
[0025] Furthermore, the preparation method of the perovskite absorption layer in step (4) is: first spin-coating a lead iodide solution or a mixed solution of lead iodide and cesium iodide, and after preliminary annealing, spin-coating a mixed solution of iodomethylformamidine and chloromethylamine, or a mixed solution of iodomethylformamidine, chloromethylamine and iodomethylamine, and annealing again.
[0026] The beneficial effect of adopting the above-mentioned further technical scheme is as follows: the present invention generates a perovskite absorption layer by first spin-coating a precursor solution containing lead iodide and then spin-coating an organic salt solution, wherein FAI is the main component of the organic salt, and MACl and MAI assist the perovskite crystallization in the annealing stage, thereby effectively realizing the passivation of defects and solving the problem that shallow energy level defects are easily formed when preparing perovskite materials in the prior art.
[0027] Furthermore, in step (4), SnO 2 The thickness of the electron transport layer is 20-100nm; the thickness of the perovskite absorption layer is 500-1000nm; the thickness of the hole transport layer is 150-300nm; the thickness of the molybdenum oxide layer is 10-20nm; and the thickness of the silver electrode is 100-200nm.
[0028] Preferably, the thickness of the silver electrode is 140 nm.
[0029] A defect-passivated perovskite solar cell is prepared by the above preparation method.
[0030] The present invention has the following beneficial effects:
[0031] The present invention provides a method for improving the performance of perovskite solar cells by defect passivation, which effectively solves the existing 2 The method of passivating the defects in the device has the problem of a large number of defects. By passivating the defects in the device, the non-radiative recombination of the device is reduced, the carrier transmission capacity is improved, the hysteresis effect of the solar cell is effectively suppressed, and the photoelectric conversion efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of the structure of a defect-passivated perovskite solar cell prepared in an embodiment of the present invention;
[0033] Figure 2 This is a schematic diagram of the structure of a perovskite solar cell obtained in a comparative example of the present invention;
[0034] Figure 3 It is the JV curve diagram of the battery in the test example. DETAILED DESCRIPTION
[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] Embodiment 1:
[0037] A method for preparing a defect-passivated perovskite solar cell comprises the following steps:
[0038] (1) Preparation of SnO 2 Electron transport layer
[0039] ① Organic hydrochloride doped SnO 2 Preparation of precursor solution: First, 12% SnO 2 The aqueous solution colloid was diluted to one-fourth of the original volume with deionized water; then 5 mg of pentamidine hydrochloride (PAD) was dissolved in 1 mL of isopropanol to obtain a PAD solution; finally, 100 μL of the diluted SnO 2 114.3 μL PAD solution was added to the aqueous solution to obtain PAD-doped SnO 2 Precursor solution.
[0040] ② Pretreatment of substrate materials: The ITO transparent conductive glass was ultrasonically cleaned with cleaning solution, deionized water, acetone and isopropanol for 40 minutes each, dried with nitrogen and placed in a UV ozone machine for UV oxygenation treatment for 20 minutes.
[0041] ③SnO 2 Electron transport layer processing: First, use PAD-doped SnO on the surface of the pre-treated ITO transparent conductive glass. 2 The precursor solution was spin-coated at a speed of 5000 rpm for 30 seconds, and then placed on a 150°C hot plate for annealing for 30 minutes at an ambient temperature of 27°C and a humidity of 30%. Finally, the annealed material was treated with UV ozone for 10 minutes and then moved into a glove box to obtain SnO 2 Electron transport layer.
[0042] (2) Preparation of perovskite absorption layer
[0043] ① Preparation of halogen compound solution: prepare a lead iodide solution with a concentration of 692 mg / mL, the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 9:1, and stir with a magnetic stirrer for 2 hours after mixing.
[0044] ② Preparation of a mixed solution of FAI, MACl and MAI: Dissolve 90 mg of iodomethylformamidine (FAI), 9 mg of chloromethylamine (MACl) and 6.39 mg of iodomethylamine (MAI) in 1 mL of isopropanol and stir with a magnetic stirrer for 1 h.
[0045] ③ Preparation of perovskite absorption layer: Spin-coat 40 μL of lead iodide solution on SnO 2 The electron transport layer was spin-coated under the following conditions: a rotation speed of 1500 rpm and a time of 30 s; after spin coating, annealing was performed in a glove box at a temperature of 70°C and a time of 1 min; then 40 μL of a mixed solution of FAI, MACl and MAI was spin-coated on the annealed lead iodide film under the following conditions: a rotation speed of 2300 rpm and a time of 30 s; annealing was performed in air at a temperature of 125°C and a time of 15 min, and the annealing environment humidity was 35%, thereby obtaining a perovskite absorption layer.
[0046] (3) Preparation of hole transport layer
[0047] ① Preparation of hole transport layer Spiro-OMeTAD precursor solution: 72.3 mg of 2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD), 9 mg of tri[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tri(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide) (Fk209), 30 μL of tributyl phosphate (tBP), 35 μL of lithium salt solution and 1 mL of chlorobenzene were mixed evenly to obtain a solution; wherein, the lithium salt solution was prepared by dissolving 260 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile.
[0048] ② Preparation of hole transport layer: Take 40 μL of hole transport layer Spiro-OMeTAD precursor solution and spin coat it on the perovskite absorption layer at a spin coating speed of 3000 rpm for 30 seconds, then place it in a drying cabinet at 26°C and 1% humidity and dry it for 2 hours.
[0049] (4) Vacuum deposition electrode
[0050] First, a molybdenum oxide layer was deposited on the hole transport layer by vacuum evaporation with a vacuum degree of 10 -5 Pa, the evaporation rate was 0.05 nm / s, the total evaporation thickness was 20 nm, and a molybdenum oxide layer was obtained.
[0051] Then, the metal electrode Ag is deposited on the molybdenum oxide layer by vacuum evaporation, and the vacuum degree is 1.4×10 -4Pa, evaporation rate of 0.15nm / s, total evaporation thickness of 140nm, defect passivation perovskite solar cell was obtained, the structural diagram is shown in Figure 1 shown.
[0052] Embodiment 2:
[0053] A method for preparing a defect-passivated perovskite solar cell comprises the following steps:
[0054] The preparation method is the same as that of Example 1, except that the SnO doped with PAD in step (1) is 2 The volume of the PAD solution in the precursor solution was changed to 131.7 μL.
[0055] Embodiment 3:
[0056] A method for preparing a defect-passivated perovskite solar cell comprises the following steps:
[0057] The preparation method is the same as that in Example 1, except that the PAD solution in step (1) is replaced by a methoxylamine hydrochloride aqueous solution with a concentration of 20 mg / mL; the mixed solution of FAI, MACl and MAI in step (2) is replaced by a mixed solution of FAI and MACl, and the preparation method of the mixed solution of FAI and MACl is as follows: 90 mg of iodomethylformamidine (FAI) and 18 mg of chloromethylamine (MACl) are dissolved in 1 mL of isopropanol and stirred with a magnetic stirrer for 1 h; the hole transport layer Spiro-OMeTAD precursor solution in step (3) is replaced by a hole transport layer P3HT precursor solution, and the preparation method of the hole transport layer P3HT precursor solution is as follows: 15 mg of [poly (3-hexylthiophenol)] (P3HT), 30 μL of tributyl phosphate (tBP), 35 μL of lithium salt solution and 1 mL of chlorobenzene are mixed evenly, and the preparation method of the lithium salt is the same as that in Example 1.
[0058] Embodiment 4:
[0059] A method for preparing a defect-passivated perovskite solar cell comprises the following steps:
[0060] The preparation method is the same as that of Example 1, except that the PAD solution in step (1) is replaced by a 20 mg / mL 3-chloropropylamine hydrochloride aqueous solution; the halogen compound solution in step (2) is replaced by a mixed solution of 742.2 mg / mL lead iodide and 19.8 mg / mL cesium iodide, and the solvent is a mixed solvent of DMF and DMSO in a volume ratio of 9:1.
[0061] Comparative Example 1:
[0062] A method for preparing a perovskite solar cell comprises the following steps:
[0063] The preparation method is the same as that of Example 1, except that in step (1), SnO 2 When the electron transport layer is formed, the diluted tin oxide solution is directly used as the electron transport layer precursor solution to prepare a perovskite solar cell. The structural diagram is shown in FIG. Figure 2 shown.
[0064] Test example:
[0065] The perovskite solar cells prepared in Example 1 and Comparative Example 1 were analyzed and tested using a solar simulator produced by Zhuoli Hanguang. The light source was a 500W xenon lamp. The incident light was calibrated using a KG-5 standard silicon cell. The light intensity incident on the cell during the test was kept at a standard sunlight intensity (AM1.5 G, 100mW / cm 2 ) intensity. Voltage was applied to both ends of the battery. The voltage applied during forward scanning was 0-1.2V, and the voltage applied during reverse scanning was 1.2-0V. The current was collected by Keithley 2400, and the JV curve of the battery was finally obtained.
[0066] The experimental results are as follows Figure 3 As shown, compared with Comparative Example 1, the open circuit voltage of the perovskite solar cell prepared in Example 1 is increased from the original 1.09V to 1.13V; the fill factor is increased from 76.06% to 79.14%, and the photoelectric conversion efficiency is increased from the initial 19.45% to 21.72%, a relative increase of 11.7%. In order to obtain a universal conclusion, the photoelectric conversion efficiency of the perovskite solar cells obtained from multiple experiments was statistically analyzed. The statistical results show that compared with Comparative Example 1, the photoelectric conversion efficiency of Example 1 is effectively improved. By comparing the photoelectric performance parameters of the device, it is found that the improvement in photoelectric conversion efficiency is attributed to the improvement of open circuit voltage and fill factor. This is because doping effectively passivates defects in the device, reduces non-radiative recombination of the device, and improves the carrier transmission capacity. At the same time, the hysteresis effect of the perovskite solar cell is also significantly suppressed.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a defect-passivated perovskite solar cell, characterized in that: The following steps are involved: (1) mixing a SnO2 aqueous solution and an organic hydrochloride solution, and ultrasonicating the mixture to obtain an organic hydrochloride-doped SnO2 precursor solution; (2) preparing a halogen compound solution and an organic salt solution as a perovskite precursor solution; (3) Fk209, tributyl phosphate, lithium salt, Spiro-OMeTAD and chlorobenzene or tributyl phosphate, lithium salt, P3HT and chlorobenzene are uniformly mixed to obtain a hole transport layer precursor solution; (4) On a substrate material, a SnO2 electron transport layer, a perovskite absorption layer and a hole transport layer are prepared by spin coating the organic hydrochloride-doped SnO2 precursor solution obtained in step (1), the perovskite precursor solution obtained in step (2) and the hole transport layer precursor solution obtained in step (3) in sequence, followed by oxidation, and finally preparing a molybdenum oxide layer and a silver electrode on the hole transport layer to obtain a SnO2 electron transport layer.
2. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: The mass concentration of the SnO2 aqueous solution in the step (1) is 1-5%; the organic hydrochloride includes any one of pentamidine hydrochloride, chloromethylamine, methoxyamine hydrochloride, propylamine hydrochloride and 3-chloropropylamine hydrochloride; the solvent of the organic hydrochloride solution is isopropanol or water; the volume ratio of the SnO2 aqueous solution to the organic hydrochloride solution is 1-2:1-50.
3. The method for preparing a defect-passivated perovskite solar cell according to claim 2, characterized in that: The concentration of the pentamidine hydrochloride solution is 3-7 mg / mL, and the solvent is isopropanol; the concentration of any one of the solutions of chloromethylamine, methoxyamine hydrochloride, propylamine hydrochloride and 3-chloropropylamine hydrochloride is 15-25 mg / mL, and the solvent is water.
4. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: In the step (2), the halogen-containing compound is lead iodide or a mixture of lead iodide and cesium iodide, the organic salt is iodomethylformamidine, chloromethylamine, or a mixture of iodomethylformamidine, chloromethylamine, and iodomethylamine; the solvent of the halogen-containing compound solution is a mixed solvent of DMF and DMSO, the concentration of lead iodide is 600-700 mg / mL, and the concentration of cesium iodide is 0-25 mg / mL; the solvent of the organic salt solution is isopropanol, and the mass ratio of the organic salt iodomethylformamidine to chloromethylamine is 70-100:6-20, or the mass ratio of iodomethylformamidine, chloromethylamine, and iodomethylamine is 50-100:8-12:6-12. 。 5. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: In the step (3), the mass volume ratio of Spiro-OMeTAD, Fk209, tributyl phosphate, lithium salt solution and chlorobenzene is 65-80 mg: 5-15 mg: 20-40 μL: 25-45 μL: 0.5-2 mL; the mass volume ratio of P3HT, tributyl phosphate, lithium salt solution and chlorobenzene is 10-20 mg: 20-40 μL: 25-45 μL: 0.5-2 mL.
6. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: The lithium salt solution is an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide with a concentration of 200-300 mg / mL.
7. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: In the step (4), the substrate material is ITO transparent conductive glass, which is subjected to ozone treatment before spin coating, and the treatment time is 10-40 minutes.
8. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: In the step (4), the spin coating speed of the SnO2 electron transport layer is 3000-6000 rpm, the spin coating time is 10-60s, and the layer is annealed at 90-170°C for 15-45min after spin coating; in the perovskite absorption layer, the spin coating speed of the halogen compound solution is 1000-2000 rpm, the spin coating time is 10-60s, and the layer is annealed at 50-90°C for 0.5-5min after spin coating; the spin coating speed of the organic salt is 1500-3000 rpm, the spin coating time is 10-60s, and the layer is annealed at 100-150°C for 10-30min after spin coating; the spin coating speed of the hole transport layer is 1500-5000 rpm, the spin coating time is 10-60s, and the oxidation time is 1-15 hours.
9. The method for preparing a defect-passivated perovskite solar cell according to claim 1, characterized in that: In the step (4), the thickness of the SnO2 electron transport layer is 20-100nm; the thickness of the perovskite absorption layer is 500-1000nm; the thickness of the hole transport layer is 150-300nm; the thickness of the molybdenum oxide layer is 10-20nm; and the thickness of the silver electrode is 100-200nm.
10. A defect-passivated perovskite solar cell, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Triethylamine hydrochloride modified perovskite solar cell and preparation method thereof
CN113193124A
Perovskite solar cell and preparation method thereof
CN115188893A
Perovskite solar cell and preparation method thereof
CN115295727A
Perovskite solar cell and preparation method thereof
CN116133441A
Betaine hydrochloride modified SnO2-based perovskite solar cell and preparation method thereof
CN116456734A
Cited By
Large-area hybrid perovskite photovoltaic cell and preparation method thereof
CN121772478A
Large-area hybrid perovskite photovoltaic cells and methods of making the same
CN121772478B